2018
DOI: 10.1038/s41598-018-28987-6
|View full text |Cite
|
Sign up to set email alerts
|

A lower dose of intravitreal conbercept effectively treats retinopathy of prematurity

Abstract: Intravitreal Conbercept (IVC) is the latest applied and effective treatment for the management of retinopathy of prematurity (ROP). However, conbercept escapes from the vitreous into the general circulation and reduce systemic VEGF concentrations. Thus, there are concerns about systemic complications, in these premature infants who are developing vital organ systems. This study is to determine whether a low dosage (0.15 mg/0.015 mL) of IVC is effective in the treatment of Zone II Stage 2/3 + ROP. A total of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In this study, recurrence that required treatment occurred in 9 patients (15 eyes, 12.82%) with ROP. Our previous studies 6,7 of conbercept demonstrated similar ROP recurrence rates (6/38 and 3/20, respectively), which were consistent with a study from another team in South China (8/48). 8 In our comparative study, 7 the recurrence rate was lower with conbercept than with ranibizumab (15/28, 53.6%).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, recurrence that required treatment occurred in 9 patients (15 eyes, 12.82%) with ROP. Our previous studies 6,7 of conbercept demonstrated similar ROP recurrence rates (6/38 and 3/20, respectively), which were consistent with a study from another team in South China (8/48). 8 In our comparative study, 7 the recurrence rate was lower with conbercept than with ranibizumab (15/28, 53.6%).…”
Section: Discussionsupporting
confidence: 89%
“…The same amplitude of serum VEGF level variation in preterm infants could be not significant, while that in adults could be significant statistically. Considering our previous study suggested 0.15 mg IVC was effective for Zone II Stage 2/3 + ROP, [6] reducing the doses of the anti-VEGF agents appear to be safer choices for less serum VEGF suppression. Moreover, there's no difference in serum VEGF concentrations between ROP patients with recurrence and the rest before and after IVC treatment.…”
Section: Discussionmentioning
confidence: 90%
“…A few studies indicated that intravitreal anti-VEGF drugs induce systemic VEGF suppression for weeks to months, [3][4][5] though no significant adverse events have been reported so far. The use of conbercept, a novel anti-VEGF agent, for ROP treatment has been rarely reported; [6][7][8] however, the effect of conbercept for systemic VEGF concentration in ROP has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have proven the effectiveness of anti‐VEGF agents (conbercept, ranibizumab and bevacizumab) in the treatment of ROP (Mintz‐Hittner et al, 2011; Huang et al, 2017; Feng et al, 2017; Cheng et al, 2018; Jin et al, 2018; Bai et al, 2019; Stahl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Conbercept is a novel recombinant fusion protein designed as a decoy receptor composed of the second Ig domain of VEGF receptor 1 and the third and fourth Ig domains of VEGF receptor 2 fused to the constant region (Fc) of human IgG1 (Zhang et al, 2009). Recently, several studies have demonstrated it is effective and safe in the treatment of ROP with conbercept (Cheng et al, 2018; Jin et al, 2018; Bai et al, 2019). Yong et al demonstrated that a total of 38 eyes (20 infants) were treated by intravitreal conbercept.…”
Section: Introductionmentioning
confidence: 99%